2018
DOI: 10.1186/s13071-018-2812-x
|View full text |Cite
|
Sign up to set email alerts
|

Feline gastrointestinal parasitism in Greece: emergent zoonotic species and associated risk factors

Abstract: BackgroundFeline gastrointestinal parasitism constitutes an issue of concern for veterinarians since parasites are widespread and affect animals’ health and welfare. Furthermore, some of these pathogens have zoonotic potential. To provide detailed data on the current epizootiology of feline endoparasitism, a multicentric survey was conducted during 2016.MethodsFaeces from 1150 cats were collected from all regions of Greece and examined by sedimentation and flotation techniques. Possible risk factors including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 75 publications
(139 reference statements)
9
42
2
2
Order By: Relevance
“…Toxocara cati larvae that harbor in different tissues or organs of the paratenic hosts, such as small mammals or birds [ 40 ], once ingested by the definitive host, develop and reach adult stages in the small intestines [ 17 ]. Sex was not found to be a risk factor and the same results were obtained by others [ 11 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Toxocara cati larvae that harbor in different tissues or organs of the paratenic hosts, such as small mammals or birds [ 40 ], once ingested by the definitive host, develop and reach adult stages in the small intestines [ 17 ]. Sex was not found to be a risk factor and the same results were obtained by others [ 11 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…Different studies have identified T. cati as the most frequently found parasite in domestic cats [ 13 , 26 ]. In Europe, T. cati prevalence varies between 7.2 and 83.3% with an average prevalence of 17.8% [ 11 , 26 , 27 , 28 ]. The prevalence of T. cati in household/owned and asymptomatic cats in Romania lies in the reported average for Europe according to this study and a previous one (20.3%) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study of 2775 dog faecal samples from the Lazio Region of central Italy (1156 from households and 1619 from shelter dogs) only 0.1% were found to be infected [16]. In Greece, in a study of the faeces from 1150 cats, a prevalence of 0.2% was detected [47]. However, the poor sensitivity of coproscopy means that faecal analysis is likely to significantly underestimate infection by Dipylidium .…”
Section: Discussionmentioning
confidence: 99%
“…In small animal practice, G. intestinalis is often recognised as the most frequently detected enteric parasite (Bouzid et al, 2015;Palmer et al, 2008). The prevalence ranges between 0-30% and this frequency of detection is highlighted by G. intestinalis prominent place in diagnostic PCR faecal panels offered to veterinarians by diagnostic laboratories (Feng and Xiao, 2011;Gizzi et al, 2014;Gruffydd-Jones et al, 2013;Ito et al, 2016;Koehler et al, 2014;Symeonidou et al, 2018;Tysnes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%